Analysis of the Strength of the Upper Structure Due to the Addition of Floors to the First Middle School Building in Pekanbaru City - Puspita Sari, Neri; Setiani, Yulia; Ikmal, Ahmad (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2024)
This research was carried out on the example of a Junior High School building in Pekanbaru City with an initial structure of 2 floors and engineered by adding floors vertically to become 3 floors, with the aim that when the existing building has additional floors, it will be able or not able to support the additional floor load. Then the analysis was carried out using the ETABS software modeling method based on the regulations SNI 2847:2013, SNI 1726:2019, 2052:2017 and SNI 1727:2020. The building plan has an area of 34 x 9.5 m2 with a building height of 4 m per floor. with concrete quality fc' 18.68 MPa or K225, steel quality fy 280 MPa for reinforcement smaller than 10 mm, fy 420 MPa for reinforcement diameter greater than 10 mm. The results of the initial structural analysis include the columns being able to accept the loads acting on the initial structure before the addition of floors. After the addition of the floor, the structure becomes unable to accept the loads acting on the structure, so structural strengthening of the beams and columns is needed. By changing the dimensions of column K1 to 30x50 cm2 the structure is able to withstand the additional floor load.